Development Of Effective Spore Induction Methods For Asporogenic Fungal Species Using The Standard Culture Medium - Tan, Kathrine Xin Yee (2018)
Factors enhancing anamorph spore production were challenged. Effects of types of media and lighting conditions in the induction of Cercospora citrullina Cooke conidiation as well as effects of banana leaf-piece agar (BLA) in the induction of Fusarium spp. macroconidia production were studied. C. citrullina isolated from pumpkin leaves with Cercospora leaf spot disease (CLS) was found unable to produce conidia when cultured on potato dextrose agar. Pathogenicity test was carried out on several cucurbit host plants prior to the study on effect of culture medium and substrates under different lighting conditions in inducing the conidiation of C. citrullina.